The importance of biochemical indicators in determining male infertility - Nazarova, Gunay Elshan (European Journal of Clinical and Experimental Medicine, 2024)
<p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Introduction and aim. Recently, infertility has become a global problem and the frequency of the “male” factor in family infertility has reached 40-50%. The aim of the research is to investigate the role of some biochemical indicators (endocrine factors and fructose) in determining male infertility. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Material and methods. In the study, the spermogram of 101 men aged 20–46 with idiopathic male infertility, the concentration of follicle-stimulating hormone (FSH), luteinizing hormone (LH), prolactin and testosterone hormones in their blood, and the concentration of fructose in their sperm samples were analyzed, and their correlations were determined. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Results. The concentration of FSH in the blood serum of men with asthenozoospermia and oligozoospermia increased statistically significantly by 57.7% and 2.4 times, respectively, compared to the control. More serious endocrinological disorders were recorded in men with azoospermia. In men with non-obstructive azoospermia, the concentration of FSH is 8.8 times, that of LH is 2.9 times; while prolactin increased by 89.0% compared to the control, testosterone concentration decreased by 22.9%. The fructose concentration in the oligozoospermia group compared to the control group increased by 60.8% (pH1<0.001), and in the non-obstructive azoospermia group by 2.0 times (pH1=0.001). A positive correlation between FSH and LH and a negative correlation between fructose concentration and forward motility of spermatozoa were determined in both asthenospermic and oligozoospermic patients (ρ=0.544; p=0.002). In case of non-obstructive azoospermia, FSH and prolactin, in azoospermia, LH and testosterone were directly proportional. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Conclusion. During male infertility, there is a serious relationship between sperm indicators and endocrine disorders. An increase in the concentration of fructose is the main indicator of a decrease in the number and motility of spermatozoa. A high concentration of FSH and LH in men with azoospermia can be considered one of the important indicators in the diagnosis of non-obstructive azoospermia.